The aetiology of rickets-like lower limb deformities in Malawian children. Issue 7 (July 2016) - Braithwaite, V.; Freeman, R.; Greenwood, C.; Summers, D.; Nigdikar, S.; Lavy, C.; Offiah, A.; Bishop, N.; Cashman, J.; Prentice, A.
Abstract Summary Debilitating rickets-like lower limb deformities are common in children throughout the world, particularly in Malawi, Africa where the causes are unknown. We have identified that Blount disease and calcium deficiency rickets are the likely causes of these deformities and propose calcium supplementation as a potential treatment of Malawian rickets. Introduction Surgical correction of rickets-like lower limb deformities is the most common paediatric operation performed at Beit Cure Orthopaedic Hospital, Malawi. The aim of this study was to investigate the aetiology of these deformities. Methods Children with a tibio-femoral angle of deformity >20° were enrolled (n = 42, 3.0–15.0 years). Anthropometric and early life and well-being data were collected. Early morning serum and urine samples were collected on the morning of the operation for markers of calcium and phosphate homeostasis. Knee radiographs were obtained, and the children were diagnosed with either Blount (BD, n = 22) or evidence of rickets disease (RD, n = 20). As BD is a mechanical rather than metabolic disease, BD were assumed to be biochemically representative of the local population and thus used as a local reference for RD. Results There were no differences in anthropometry or early life experiences between BD and RD. Parathyroid hormone (PTH), 1, 25-dihydroxyvitamin D, total alkaline phosphatase and urinary phosphate were significantly higher and serum phosphate, 25-hydroxyvitamin D (25OHD) and tubular maximal reabsorption of phosphate significantly lower in RD than BD. There was no difference in serum calcium, fibroblast growth factor 23 or markers of iron status between groups. All children had 25OHD > 25 nmol/L. Conclusions Vitamin D deficiency is not implicated in the aetiology of RD or BD in Malawian children. The cause of RD in Malawi is likely to be dietary calcium deficiency leading to elevated PTH resulting in increased losses of phosphate from the bone and glomerular filtrate. The causes of BD remain unclear; there was no evidence in support of previously suggested risk factors such as being overweight or starting to walk early. Prior to surgical intervention, supplementation with calcium should be considered for children with RD.